Ethical issues in online interpreting training - Liu Hongyan; Lei Zhenhui (Journal of China Computer-Assisted Language Learning)
Although online education dissolves boundaries by providing “anywhere and anytime” teaching and learning opportunities, ethical concerns and challenges still exist. Interpreting training is preferably achieved in a face-to-face setting, as it concentrates on individual practice within an authentic interpreting environment for skill development rather than mere knowledge acquisition. This study examines ethical challenges and concerns in online interpreting training, including equality of learning outcomes, emotional support, privacy and audio/video data protection, and misconduct behaviours. Based on the observation of such ethical concerns, possible solutions for addressing such issues in the context of online interpreting training are explored. We suggest developing professional interpreting learning platforms and software, adopting virtual reality technology, compiling a multimodal corpus, and establishing a virtual community to achieve better learning outcomes.